Development of Emotion Regulation Neural Circuitry: Anatomical Volumes and Functional Connectivity in Middle Childhood - Hall, Alexander William Milne (My University, 2014)
Part 1 - Background: Maternal prenatal adversity often results in changes to the hypothalamic- pituitary-adrenal axis (HPA axis) function, such as greater cortisol secretion. Recent evidence suggests that fetal exposure to elevated cortisol levels may cause structural changes to key limbic regions integral to regulation of the HPA axis such as the amydala and hippocampus in children. In the early postnatal months these same structures are particularly vulnerable to the quality of maternal care and parenting styles. However, the relative impact and interaction of such factors is still underreported. Methods: 24 healthy 7-8 year old children (male:female=13:11) underwent an MRI. Amygdala and hippocampal volumes were assessed and used in multiple regression models to determine the impact of prenatal cortisol and postnatal maternal sensitivity. Results: Larger right hippocampal volumes were associated with increases in late gestation cortisol levels (4.6 mm3/nmol of cortisol; FDR corrected p<0.005). Increases in 6th month maternal sensitivity predicted a decrease in right hippocampal volumes at a trend level (FDR corrected p=0.09). There was no interaction effect between cortisol and sensitivity. There were no significant effects on left hippocampus or bilateral amygdala volumes. No sex differences were noted. Discussion: Given previous work we had expected greater amygdala volume and reduced hippocampal volumes to associate with increases in cortisol and decreases in sensitivity. Our results suggest that there may indeed be a programming effect on children’s hippocampi by prenatal cortisol. Findings may be reflective of a positive adaptive response or resilience to adverse prenatal environments. Part 2 - Introduction: Emotion regulation (ER) is an integral component to mental health. ER is thought to incorporate limbic as well prefrontal regions in several cognitive top-down circuits to utilize higher-order executive functions to adequately monitor and inhibit emotion when necessary. However, only recently has research targeted the developmental trajectories of these circuits from childhood. Methods: 29 healthy children aged 7-8 years (mean 7.34 ± 0.48) underwent functional magnetic resonance imaging (fMRI) with an implicit emotion go/nogo cognitive task to assess the developmental state and interaction between cognitive and emotional circuitry using functional connectivity (FC) in this age group. Results: Central executive networks (CEN) and salience networks (SN) showed more diffuse FC than mature networks, with greater inter-network connectivity. During exposure to fearful stimuli, there was greater connectivity within CEN and SN during go trials. Nogo trials were associated with more limbic-cognitive network interaction during concurrent exposure to fearful stimuli than neutral stimuli, Connectivity with the dACC was found to be common between limbic and CEN seeded networks. Discussion: Results indicate that cognitive networks are present but generally less mature than previous results from adult populations. Particularly, diffuse connectivity between the insula and PCC was negatively correlated indicating a developing switch between resting and salience networks. Additionally, greater connectivity for response inhibition tasks (nogo) during fearful stimuli exposure in the dACC, amygdala, anterior prefrontal, and DLPFC, suggests a maturing emotion regulation network, capable of managing cognitive tasks during emotional stimuli presentation.
Keywords: fMRI; brain development; cortisol; maternal sensitivity; functional neural networks